Effect of Internal Control Structure Application Towards the Efficiency of Credit Distribution on Save Loans Cooperative (KSP) In Sukawati District - Danayanti, Ni Luh Intan; Mahaputra, Nyoman Kusuma Adnyana; Sunarwijaya, I Ketut (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2020)
This study aims to determine the effect of the application of internal control structures on the efficiency of lending. This research was conducted in all savings and loan cooperatives of Sukawati Subdistrict registered with the Gianyar Regency Cooperative Service. The sampling technique used is saturated sampling. The sample in this study amounted to 68 respondents from 34 populations. The data analysis technique is multiple linear regression analysis. The results showed the control environment, risk assessment, and monitoring variables had a positive effect on the efficiency of lending. Whereas Control, Information and Communication activities do not affect the efficiency of credit distribution to savings and loan cooperatives.